2018
DOI: 10.21608/jappmu.2018.35742
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Rocket Oil Addition on Productive and Reproductive Performance of Growing Ram Lambs Under Hot Climate Condition.

Abstract: Twenty-four crossbred ram lambs (1/2 Finnish Landrace ×1/2 Rahmani) aged 3-4 months and averaged 22.25±0.93 kg live body weight were randomly divided into three treatments (8 lambs in each) according to their live body weight. The experimental period lasted 6 months from May to October 2015. Ram lambs were orally treated with 0 (control), 1 (T1) and 2 (T2) mg rocket oil (RO)/kg LBW. Growth performance, puberty and semen characteristics of ram lambs, some blood parameters and economic efficiency were estimated.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 15 publications
2
10
0
Order By: Relevance
“…(32). this result was consistent with those reported by El-Badawy et al (11) and El-Madawy et al, (12) that feeding on oils high in unsaturated fatty acids led to a significant increase in the size of the testicle and scrotum circumference. It also agreed with El-Zelaky et al (10) that feeding lambs on a low degradable jatropha cake led to a significant increase in scrotum size, while Dantos et al (8) observed that the age or weight at puberty was not affected by the increased protein and energy intake (1).…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…(32). this result was consistent with those reported by El-Badawy et al (11) and El-Madawy et al, (12) that feeding on oils high in unsaturated fatty acids led to a significant increase in the size of the testicle and scrotum circumference. It also agreed with El-Zelaky et al (10) that feeding lambs on a low degradable jatropha cake led to a significant increase in scrotum size, while Dantos et al (8) observed that the age or weight at puberty was not affected by the increased protein and energy intake (1).…”
Section: Resultssupporting
confidence: 91%
“…El-Zelaky et al (10) noticed that feeding lambs a low degradable jatropha cake led to a significant increase in testosterone concentration during 115-275 days of old, this may be due to changes in testicular size resulting from an increased protein supply, which is positively correlated with changes in gonadotrophin and testosterone secretion (31). On other hand the results did not agree with the result of El-Badawy et al (11), Behery et al,(4) mentioned that increasing the percentage of low degradable fat did not have a significant effect on cholesterol and triglycerides in the blood. Table 4.…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…Supplemented groups, regardless of substance, had similar values of serum oxidative markers to NC groups not exposed to OS, and higher values than PC exposed to oxidative stress factors. Increases in the oxidative stress markers in Ro1 and Ro2 are probably due to the presence of antioxidant substances in rocket salad, such as total phenols ( Table 2 ), which participated in the reduction in the toxic influences in different mechanisms and removal of the deleterious impacts of oxidative factors [ 50 , 51 ]. This might also be the protective effect of flavonoid compounds in rocket salad against stress conditions and immune inhibition, which have important roles in mediating the boosting of inflammatory cytokines and counteracting the stress [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the lowering of MDA in the liver was noticed, and elevated liver antioxidant enzymes including glutathione S-transferase (GST), SOD, and GPX resulted from giving rocket salad in four different forms (leaves and seed powders by 5% each instead of cellulose diet or in juice or oil forms by 300 mg or 3 mL/kg of body weight, respectively) in rats exposed to liver damage by paracetamol [ 53 ]. In ram lambs, the increase in serum total antioxidant capacity was recorded after 6 months of feeding with 2 mg of rocket salad oil during hot climate stress [ 50 ]. Under thermal stress conditions, it was found that 3% dietary rocket salad leaves enhanced liver SOD and CAT activities with a depression in MDA and cortisol levels in Oreochromis niloticus fish.…”
Section: Discussionmentioning
confidence: 99%